Functional Amyloids - Otzen, Daniel; Riek, Roland (Cold Spring Harbor perspectives in biology, 2019)
When protein/peptides aggregate, they usually form the amyloid state consisting of cross β-sheet structure built by repetitively stacked β-strands forming long fibrils. Amyloids are usually associated with disease including Alzheimer's. However, amyloid has many useful features. It efficiently transforms protein from the soluble to the insoluble state in an essentially two-state process, while its repetitive structure provides high stability and a robust prion-like replication mechanism. Accordingly, amyloid is used by nature in multifaceted and ingenious ways of life, ranging from bacteria and fungi to mammals. These include (1) Structure: Templating for small chemical molecules (Pmel17), biofilm formation in bacteria (curli), assisting aerial hyphae formation in streptomycetes (chaplins) or monolayer formation at a surface (hydrophobins). (2) Reservoirs: A storage state for peptide/proteins to protect them from their surroundings or vice versa (storage of peptide hormones in mammalian secretory granules or major basic protein in eosinophils). (3) Information carriers: The fungal immune system (HET-s prion in , yeast prions) or long-term memory (e.g., mnemons in yeast, cytoplasmic polyadenylation element-binding protein in aplysia). Aggregation is also used to (4) "suppress" the function of the soluble protein (e.g., Cdc19 in yeast stress granules), or (5) "signaling" through formation of oligomers (e.g., HET-s prion, necroptosis-related proteins RIP1/RIP3). This review summarizes current knowledge on functional amyloids with a focus on the amyloid systems curli in bacteria, HET-s prion in , and peptide hormone storage in mammals together with an attempt to highlight differences between functional and disease-associated amyloids.